The Tests of Time 2017
DOI: 10.2307/j.ctvcm4h07.24
|View full text |Cite
|
Sign up to set email alerts
|

Hans Christian Oersted

Abstract: The pervasive integration of Unmanned Aerial Vehicles (UAVs) across multifarious domains necessitates a nuanced understanding of control methodologies to ensure their optimal functionality. This exhaustive review meticulously examines two pivotal control paradigms in the UAV landscape-Geometric Control and Feedback Linearization. Delving into the intricate theoretical underpinnings, practical applications, strengths, and challenges of these methodologies, the paper endeavors to provide a comprehensive overview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Around a conducting wire with a static current, Oersted [7] discovered in 1820 that the orientation of a compass changes, but surprisingly without any contact between the magnet and the wire [8]. Oersted and fellow scientists among which Biot, Savart and Ampere have shown that the field around an infinite electrical wire [9] [10] (in 5.2.2), varies in I/r, which is the ratio of the current by the distance from the wire.…”
Section: Infinite Wire With An Electrical Currentmentioning
confidence: 99%
“…Around a conducting wire with a static current, Oersted [7] discovered in 1820 that the orientation of a compass changes, but surprisingly without any contact between the magnet and the wire [8]. Oersted and fellow scientists among which Biot, Savart and Ampere have shown that the field around an infinite electrical wire [9] [10] (in 5.2.2), varies in I/r, which is the ratio of the current by the distance from the wire.…”
Section: Infinite Wire With An Electrical Currentmentioning
confidence: 99%